Dynamic recrystallization behavior of GH4169G alloy during hot compressive deformation. Issue 9 (September 2019) - Jia, Dan; Sun, Wenru; Xu, Dongsheng; Liu, Fang
Abstract: The microstructure evolutions and nucleation mechanisms of GH4169 G alloy were studied by optical microscope, electron backscatter diffraction (EBSD) and transmission electron microscope (TEM). The hot compression tests were performed different imposed reductions in the range of true strain from 0.12 to 1.2 at the temperatures of 930 ℃-1050 ℃ with strain rates of 0.01 s −1 -1 s −1 . It is found that cumulative and local misorientation increase firstly and then decrease when the strain is increased due to the progress of dynamic recrystallization (DRX). The low angle boundaries (LAGBs) rapidly develop to high angle boundaries (HAGBs) at relatively high deformation temperature or the low strain rate. There are three DRX mechanisms observed for GH4169 G alloy during hot deformation. Discontinuous dynamic recrystallization (DDRX) as the dominant mechanism for GH4169 G alloy is characterized by typical necklace structures and bulged-original boundaries. Besides, different deformation bands with dislocation cells formed in deformed matrix at low temperature and large strain, which indicates that continuous dynamic recrystallization (CDRX) contributed to the DRX process. The twin boundaries lost their coherent characteristics and provide sites for nucleation, which also accelerates the nucleation of DRX.